Cybermetric techniques to evaluate organizations using Web-based data - Orduna-Malea, Enrique; Alonso-Arroyo, Adolfo (Chandos Publishing is an imprint of Elsevier, 2018)
"Cybermetric Techniques to Evaluate Organizations Using Web-Based Data proposes a complete and multifaceted analysis model, integrating quantitative and qualitative measures (extracted from web usability, SEO and design interaction metrics and evaluations) with a purpose of finding potential correlations. It also includes metrics from new social media platforms, metrics related to the interaction among companies, impact filtering according to different entity categories, innovation and scientific activities and media presence. This model is then applied to test feasibility and accuracy. Different statistical methods and tests are also applied to guide data gathering and analysis. Proposes a new model aimed at measuring performance of private companies on the web, combining quantitative and qualitative techniques, Applies an empirical model to different environments (scientific, professional, innovation and media), providing new and original data not found elsewhere, Demonstrates both the advantages and risks of using indicators, Introduces solid statistical techniques for web data analysis, Presents a whole picture for measuring the web performance of technology companies through web metrics"--